Cost-effectiveness of community screening for glaucoma in rural India: a decision analytical model. (February 2018) - John, D.; Parikh, R.
Abstract: Objectives: Studies in several countries have demonstrated the cost-effectiveness of population-based screening for glaucoma when targeted at high-risk groups such as older adults and with familial history of disease. This study conducts a cost-effective analysis of a hypothetical community screening and subsequent treatment programme in comparison to opportunistic case finding for glaucoma in rural India. Study design: A hypothetical screening programme for both primary open-angle glaucoma and angle-closure disease was built for a population aged between 40 and 69 years in rural areas of India. Methods: A decision analytical model was built to model events, costs and treatment pathways with and without a hypothetical screening programme for glaucoma for a rural-based population aged between 40 and 69 years in India. The treatment pathway included both primary open-angle glaucoma and angle-closure disease. The data on costs of screening and treatment were provided by an administrator of a tertiary eye hospital in Eastern India. The probabilities for the screening and treatment pathway were derived from published literature and a glaucoma specialist. The glaucoma prevalence rates were adapted from the Chennai Glaucoma Study findings. Results: An incremental cost-effectiveness ratio value of ₹7292.30 per quality-adjusted life-year was calculated for a community-screening programme for glaucoma in rural India. The community screening for glaucoma would treat an additional 2872 cases and prevent 2190 person-years of blindness over a 10-year period. Conclusions: Community screening for glaucoma in rural India appears to be cost-effective when judged by a ratio of willingness-to-pay thresholds as per WHO-CHOICE guidelines. For community screening to be cost-effective, adequate resources, such as trained medical personnel and equipment would need to be made available. Highlights: In comparison to current practice (i.e. without a screening programme but with some opportunistic case finding), the introduction of a community-screening programme for glaucoma for 40–69 years age group is likely to be cost-effective if implemented in rural areas of India. In addition, the screening programme could treat additional cases and preserve sight, in comparison with no screening. Grant-making organisations and government could use the results and model to choose the age groups appropriate for screening given their willingness-to-pay for a quality-adjusted life-year.